2020
DOI: 10.1108/ilt-03-2020-0088
|View full text |Cite
|
Sign up to set email alerts
|

Experimental analysis and modeling of viscosity and thermal conductivity of GNPs/SAE 5W40 nanolubricant

Abstract: Purpose The purpose of this study is to investigate thermal conductivity and dynamic viscosity of graphene nanoplatelet-based (GNP) nanolubricant. Design/methodology/approach Nanolubricants in concentrations of 0.025, 0.05, 0.1 and 0.5 Wt% were prepared by means of two-step method. The stability of nanolubricants was monitored by visual inspection and dynamic light scattering tests. Thermal conductivity and dynamic viscosity of nanolubricants in various temperatures between 25°C–70°C were measured with KD2-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…A temperature rise contributes to the rise in the energy level, movement and vibration of the unfilled oil molecules, weakening the molecular bonds between the lubricant layers and increasing the speed and displacement of molecules. Therefore, an increase in thermal conductivity can occur (Wadi et al, 2020). On the other hand, despite the drop in thermal conductivity being detected at temperatures of 60°C and 70°C for the concentration of 0.025 wt%, mostly, the increase in the concentration of solid particles leads to the increase in thermal conductivity.…”
Section: Resultsmentioning
confidence: 93%
“…A temperature rise contributes to the rise in the energy level, movement and vibration of the unfilled oil molecules, weakening the molecular bonds between the lubricant layers and increasing the speed and displacement of molecules. Therefore, an increase in thermal conductivity can occur (Wadi et al, 2020). On the other hand, despite the drop in thermal conductivity being detected at temperatures of 60°C and 70°C for the concentration of 0.025 wt%, mostly, the increase in the concentration of solid particles leads to the increase in thermal conductivity.…”
Section: Resultsmentioning
confidence: 93%
“…The results showed that the thermal conductivity and viscosity of the nanolubricant increased with the increase in volume fraction at a constant temperature. Also, Wadi et al [4] experimentally examined the thermophysical properties of the nanolubricant containing graphene nanoparticles for mass fractions of 0.025 to 0.5% in a temperature range of 25 to 70 °C. The results showed that the thermal conductivity and viscosity of the nanolubricant increased with the increase in mass fraction at a constant temperature.…”
Section: Referencementioning
confidence: 99%
“…Wadi et al created a graphene nanoplatelet/SAE5W40 nanolubricant using a two‐step method. [ 88 ] For 30 days, no sedimentation occurred in any of the produced samples. Figure shows the results of DLS tests for the nanolubricant.…”
Section: Dispersion Stability Evaluation Of Nanolubricantsmentioning
confidence: 99%
“…DLS analysis results for 0.025 wt% nanoparticles concentration after 7, 14, and 21 days. [ 88 ] Reproduced with permission. [ 88 ] Copyright 2020, Emerald Publishing Limited.…”
Section: Dispersion Stability Evaluation Of Nanolubricantsmentioning
confidence: 99%